Estrogen Receptor Dosage in Breast Cancer - Sabini, Graciela; Garófalo, Elsa; Martino, Idivia; Peluffo Cestau, Jorge (Cirugía del Uruguay, 1983)
lt is well known that sorne breast tumors respond to hormonetherapy. Neverthesess until a few years ago we had not an effective method to evaluate hormonesensibility. Nowadays the estrogenic receptor dosage (ER) allows us to pick out the patients for hormonetherapy with a success probability up to 80°/o.